(untitled) (ETIMA, 2025)
The article deals with the theoretical analysis of the backward impacts of photovoltaic power plants (PVPP) on the distribution system (DS), including phenomena such as increased voltage, changes caused by manipulations, flicker, harmonics, asymmetry, and commutation dips. The work is based exclusively on theoretical knowledge and available technical literature and is currently in the development stage [1]. The practical part will be carried out in a specific location in western Slovakia on a real network with overhead lines. Using SCADA and DECALK simulation tools, the impacts of connecting 1-phase and 3-phase PVPPs on voltage conditions in the network will be analyzed. The aim is to verify theoretical knowledge through calculations and simulations, quantify backward impacts according to the type of source, and identify critical operating states. It is assumed that single-phase sources may have up to six times greater impact on voltage quality than three-phase sources [1].